The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1039/d3qi01576a
|View full text |Cite
|
Sign up to set email alerts
|

Local structural environment of single-atom catalysts

Zheng Chen,
Lili Han

Abstract: Single-atom catalysts (SACs) provide opportunities for bridging the gap between homogeneous and heterogeneous catalysis, facilitating the precise structure identification of the catalytic active sites, and offering new opportunities for interpreting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 246 publications
(294 reference statements)
0
2
0
Order By: Relevance
“…In the last decade, single-atom catalysts (SACs) have received wide research interest because of their unique electronic effects, the uniform distribution of active centers, and the highest atom use efficiency. [16][17][18] Numerous results have suggested that SACs provide identifiable active sites and a perfect model for both experimental and theoretical studies. 19 In the case of electrocatalysts for ORR, the catalytic efficiency largely depends on two factors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, single-atom catalysts (SACs) have received wide research interest because of their unique electronic effects, the uniform distribution of active centers, and the highest atom use efficiency. [16][17][18] Numerous results have suggested that SACs provide identifiable active sites and a perfect model for both experimental and theoretical studies. 19 In the case of electrocatalysts for ORR, the catalytic efficiency largely depends on two factors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) have attracted considerable attention in recent years due to their ability to maximize atom utilization, exhibit distinctive electronic properties, and provide uniform and adjustable active sites. 14–30 SACs’ well-defined active sites also serve as an ideal model to gain comprehensive insights into catalytic reaction mechanisms at an atomic scale. 24–27 From a coordination chemistry perspective, the catalytic activity of SACs is closely related to their local coordination microenvironment.…”
Section: Introductionmentioning
confidence: 99%